2023
DOI: 10.1002/chem.202300569
|View full text |Cite
|
Sign up to set email alerts
|

Normal vs. Inverted Ordering of Reduction Potentials in [FeFe]‐Hydrogenases Biomimetics: Effect of the Dithiolate Bulk

Abstract: Three hexacarbonyl diiron dithiolate complexes [Fe 2 (CO) 6 (μ-(SCH 2 ) 2 X)] with different substituted bridgeheads (X=CH 2 , CEt 2 , CBn 2 (Bn=CH 2 C 6 H 5 )), have been studied under the same experimental conditions by cyclic voltammetry in dichloromethane [NBu 4 ][PF 6 ] 0.2 M. DFT calculations were performed to rationalize the mechanism of reduction of these compounds. The three complexes undergo a two-electron transfer whose the mechanism depends on the bulkiness of the dithiolate bridge, which involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
(250 reference statements)
0
3
0
Order By: Relevance
“…The rearrangement observed in 1a 2 − is consistent with the existence of a chemical event during the two-electron process, as suggested by the electrochemical study at slow scan rates. The computed redox potential for the second electron transfer is −1.20 V vs. (Fc + /Fc) which indicates that this reduction has a potential lower than the first one, as reported for its precursor [Fe2(CO)6(µ-bdt)] [ [35][36][37] and other di-iron complexes [28,[38][39][40]. The total distribution of the charge in 1a 2 − is −1.7 on the di-iron core and −0.3 on the pma ligand.…”
Section: R Review 9 Of 18mentioning
confidence: 56%
See 2 more Smart Citations
“…The rearrangement observed in 1a 2 − is consistent with the existence of a chemical event during the two-electron process, as suggested by the electrochemical study at slow scan rates. The computed redox potential for the second electron transfer is −1.20 V vs. (Fc + /Fc) which indicates that this reduction has a potential lower than the first one, as reported for its precursor [Fe2(CO)6(µ-bdt)] [ [35][36][37] and other di-iron complexes [28,[38][39][40]. The total distribution of the charge in 1a 2 − is −1.7 on the di-iron core and −0.3 on the pma ligand.…”
Section: R Review 9 Of 18mentioning
confidence: 56%
“…In parallel, diphosphines such as bma (bma = 2,3-bis(diphenylphosphino)maleic anhydride), dppen (1,2-bis(diphenylphosphino)ethene), bpcd (4,5-bis(diphenylphosphino)-4-cyclopenten-1,3dione), were combined with di-iron systems, but it was shown that they act as innocent bystanders when they are associated with di-iron {Fe 2 (CO) 4 (µ-dithiolate)} core [23][24][25]. Differently from other complexes with the general formula [Fe 2 (CO) 4 (κ 2 -chelate)(µ-dithiolate)], which either undergo ETC process (diphosphine) or a two-electron reduction centred on the di-iron core (bis-carbene) [26,27], the complexes [Fe 2 (CO) 4 (κ 2 -bipy)(µ-xdt)] (xdt = pdt (propane-1,2-dithiolate) or bdt (benzene-1,2-dithiolate)) [15,16] would reduce according to a two-electron process, with a potential inversion [28], involving the 2,2 -bipyridine ligand. The second electron would be centred on the bipy framework, unlike the first one, which would be located on the di-iron core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation